Perancangan Sistem Virtual Tour 360 Degree Pengenalan Objek Wisata Tanah Wuk Untuk Promosi Dalam Bisnis Digital - Santiari, Ni Putu Linda; Dananjaya, I Gede Agastya; Rahayuda, I Gede Surya (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2023)
Tanah Wuk offers impressive views with the beauty of green valleys, a very calm situation, and rows of hills that complement this beauty. As a place for family recreation, Tanah Wuk provides a large enough yard that can be used as a place for barbecues and playing games with the family. Therefore, with the current development of information technology, one of which is packaging information technology through multimedia, we will increase the promotional media for Tanah Wuk Tourism Objects in Sangeh Village by creating a virtual tour application that aims to introduce Tanah Wuk Tourism Objects to tourists before visiting. Information technology, through this multimedia, is a combination of data, sound, video, audio, animation, graphics, text, and sounds in which the combination of these elements can be presented via a computer. Before being developed, the design needs to be done for this information system, starting with the menu structure design, storyboards, and interface design. System design is very important to ensure that the system built can provide significant added value for the users who use it. The design is carried out starting with data collection, needs analysis, menu structure design, storyboards, and interface design. From the needs analysis, there are two users involved in making this system, namely the admin and the user. For the menu structure, there are four menus in the system: home, profile, virtual tour, and about.